Effectiveness of a Knowledge Level of Hypertension on Blood Pressure Control, Treatment Adherence, and Physical Activity of Hypertensive Individuals - Gomleksiz, Mehtap; Gomleksiz, Muhammet Ridvan; Gelen, Seyma; Uzala, Emine Sena; Yakar, Burkay (Wiley, 2025)
Individuals' knowledge and attitudes about hypertension are important in controlling blood pressure (BP) and reducing hypertension-related mortality and morbidity. The current study aimed to investigate the effect of hypertension knowledge level on treatment adherence, BP control, and physical activity of hypertensive individuals. This prospective and cross-sectional study was conducted in the Family Medicine clinic of a tertiary healthcare institution between October 2023 and April 2024. The study included 218 patients with essential hypertension. The BP of all patients was measured with a calibrated mercury sphygmomanometer, and the patients were divided into two groups: uncontrolled BP and controlled BP. The Hypertension Knowledge Level Scale (HK-LS), General Practice Physical Activity Questionnaire (GPPAQ), and Modified Morisky Medication Adherence Scale (MMMAS-6) were administered to all participants. Although 40.8% (n = 89) of the patients had their BP under control, 59.2% (n = 129) did not. The median weight of the participants whose BP was not under control was higher than those whose BP was under control (p < 0.05). A significant positive correlation was found between the hypertension knowledge score and the Morisky total score, Morisky motivation, and Morisky knowledge scores. There was a significant negative correlation between the GPPAQ score and both systolic and diastolic BP, as well as a significant positive correlation with hypertension knowledge levels. Assessing the knowledge level of hypertensive patients about their disease, recognizing their lifestyles, and questioning their habits is crucial for recommending individualized health interventions tailored to the needs and characteristics of this population.
Keywords: hypertension knowledge; medication adherence; physical activity